2017
DOI: 10.1002/yd.20251
|View full text |Cite
|
Sign up to set email alerts
|

The Unique Context of Identity‐Based Student Organizations in Developing Leadership

Abstract: This chapter addresses the important role of identity-based student organizations in developing leadership, particularly for students who may feel marginalized because of their racial/ethnic, religious, or gender identities. Understanding the influence of these groups can help leadership educators develop a more inclusive and diverse perspective on student leadership development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…However, STEM majors who served as peer mentors were not only successful in helping new students, but credited AAMP with motivation in continuing to serve others post-college. This outcome is similar to that found by the first author and Rhonda Laylo in New Directions for Student Leadership, where students engaged with identity-based student organizations formed a very tight knit sense of community that led to continued engagement with each other and their communities’ issues (Kodama & Laylo, 2017). Given the benefits these peer mentors described, how can educators attend to more experienced students and create meaningful leadership experiences that can facilitate another level of learning and development?…”
Section: Lessons From Our Studentssupporting
confidence: 79%
“…However, STEM majors who served as peer mentors were not only successful in helping new students, but credited AAMP with motivation in continuing to serve others post-college. This outcome is similar to that found by the first author and Rhonda Laylo in New Directions for Student Leadership, where students engaged with identity-based student organizations formed a very tight knit sense of community that led to continued engagement with each other and their communities’ issues (Kodama & Laylo, 2017). Given the benefits these peer mentors described, how can educators attend to more experienced students and create meaningful leadership experiences that can facilitate another level of learning and development?…”
Section: Lessons From Our Studentssupporting
confidence: 79%
“…Brennan [19] also indicated that universities should enable undergraduates to acquire the sustainable competences at the personal level. For instance, an emphasis should be given to the leadership capacity of students [20,23,25,45]. Thus, unclear promotion mechanisms may lead to the loss of talented organization managers, which hinders the achievement of organizational goals and the advancement of organizational core competence.…”
Section: Discussionmentioning
confidence: 99%
“…Student organization is a means of student management in higher education, and many scholars are focused on the advantages of involvement in organization management. They hold the view that participation in organizations can develop members' leadership, improve students' preparedness for future jobs, increase cross-racial interaction, and generate post-college civic outcomes [20][21][22][23][24][25]. In addition, some particular student organizations have attracted scholars' attention.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also demonstrated that involvement in identity‐based organizations, cultural centers, and ethnic studies courses was particularly transformative for Asian Americans whose history has often been ignored in their educational experiences (Inkelas, ; Kodama, Manzano, Poon, Sihite, ; Maramba & Palmer, ; Poon, ). Exploring culture, identity, and racism alongside peers with similar backgrounds has influenced positive developmental outcomes such as greater self‐esteem and confidence, comfort and understanding of self in context, and critical thinking skills, which in turn empower students to become more resilient and engage in leadership (Inkelas, ; Kodama & Laylo, ; Museus et al., ; Poon, ). Thus, rather than viewing them as limiting or separatist, practitioners should encourage Asian American students to join identity‐based student organizations, take ethnic studies courses, and engage with Asian American targeted programs, whether on campus or in the surrounding community.…”
Section: Revisiting Kodama Mcewen Liang and Lee ( )mentioning
confidence: 99%